Students’ Perceptions of the Scaffolding Method in an EFL Classroom: A Study of In-Service and Pre-Service Teachers’ Teaching Collaboration - Ma'unaty, Ariny; Safriani, Afida; Salim, Agus (ICONELT, 2024)
This research explores students' perceptions of the in-service and pre-service teachers’ collaboration in applying the scaffolding method for English as a foreign language (EFL) in a secondary school. This research aims to explore students' perceptions of the scaffolding method implemented collaboratively by in-service and pre-service teachers. In addition, this research aims to investigate how the scaffolding method engaged students in the learning process. This research used a quantitative research method. The data was collected from 30 students in class X and J at State Islamic High School in Surabaya through questionnaires and semi-structured interviews. The results showed that students have a positive response toward using the scaffolding method, particularly in improving their understanding of the main topic and academic performance in learning English. They believe that this method helped them organize their thoughts, create grammatically correct sentences, increase their engagement, and improve their understanding of key concepts. Furthermore, students stated that the scaffolding method increased their confidence in completing learning tasks. In addition, they considered teachers’ support and guidance as an important element in their learning experience. This study concludes that the implementation of scaffolding methods can significantly benefit EFL practitioners by fostering a more engaging and supportive learning environment for students.